The Endopolygalacturonase Gene Bcpg1 Is Required for Full Virulence of Botrytis cinerea - Arjen ten Have; Wietse Mulder; Jaap Visser; Jan A. L. van Kan (Molecular Plant-Microbe Interactions, 1998)
Botrytis cinerea, a fungus that causes diseases in over 200 plant species, secretes a number of endopolygalacturonases that have been suggested to be involved in pathogenesis. However, so far the corresponding genes have not been isolated from this fungus. We cloned Bcpg1, encoding endopolygalacturonase, with the pgaII gene from Aspergillus niger as a heterologous probe. The Bcpg1gene is expressed to similar levels in liquid cultures of B. cinerea containing either 1% polygalacturonic acid or 1% sucrose, and is expressed during infection of tomato leaves. The Bcpg1 gene was eliminated by partial gene replacement, and the resulting mutants were tested for virulence on tomato leaves and fruits, as well as on apple fruits. Although the mutants were still pathogenic and displayed similar primary infections when compared with control strains, a significant decrease in secondary infection, i.e., growth of the lesion beyond the inoculation spot, was observed on all three host tissues. These results indicate that the Bcpg1 gene is required for full virulence.